2022
DOI: 10.3390/nu14071480
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Habitual Intake of Vitamins and New-Onset Prediabetes/Diabetes after Acute Pancreatitis

Abstract: Vitamins have many established roles in human health. However, the role of habitual dietary intake of vitamins in glucose homeostasis in individuals after acute pancreatitis (AP) is yet to be elucidated. The aim was to investigate the associations between habitual intake of fat- and water-soluble vitamins/vitamers and markers of glucose metabolism (fasting plasma glucose (FPG), homeostasis model assessment insulin resistance (HOMA-IR) index, and homeostasis model assessment β-cell function (HOMA-β)) in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…1alpha, 25-dihydroxycholecalciferol or cholecalciferol is vitamin D and its derivatives. Vitamin D deficiency is associated with cardiovascular, autoimmune, and infectious diseases 22 . Results from a cohort study of vitamin D levels and LOS in preterm infants showed that neonates with higher vitamin D levels had a lower risk of LOS than those with vitamin D deficiency, neonatal and maternal vitamin D deficiency increased the risk of LOS, and neonatal vitamin D was an independent risk factor for LOS 23 .…”
Section: Discussionmentioning
confidence: 99%
“…1alpha, 25-dihydroxycholecalciferol or cholecalciferol is vitamin D and its derivatives. Vitamin D deficiency is associated with cardiovascular, autoimmune, and infectious diseases 22 . Results from a cohort study of vitamin D levels and LOS in preterm infants showed that neonates with higher vitamin D levels had a lower risk of LOS than those with vitamin D deficiency, neonatal and maternal vitamin D deficiency increased the risk of LOS, and neonatal vitamin D was an independent risk factor for LOS 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Most nutrients do not exist on their own and are often combined with other nutrients or compounds in the human diet. Specifically, dietary fibre rarely appears on its own in natural food and is often present in the form of a plant cell wall with other nutrients (such as starch, vitamins, and minerals) [21,22]. The primary plant cell wall is the most common form of dietary fibre in the human diet, with a structured network of cellulose and hemicellulose embedded in a network of pectin, while the secondary plant cell wall is the less common form, which is made up of lignin and cellulose [23].…”
Section: Effects On Nutrients' Availabilitymentioning
confidence: 99%
“…In a more recent study, Norbitt et al [ 19 ] investigated potential connections between the intake of fat- and water-soluble vitamins with markers of glucose metabolism in patients after AP. They found a significant association between three fat-soluble vitamins (α-carotene, β-carotene, and total carotene) and homeostasis model assessment of β-cell function (HOMA-β) in patients with new-onset prediabetes/diabetes after AP[ 19 ]. Despite this association, there were no significant associations with FPG or HOMA-IR index.…”
Section: Dysfunction Of the Exocrine Pancreasmentioning
confidence: 99%
“…As deficiency of fat-soluble vitamins associated with exocrine pancreatic dysfunction may be linked to new-onset DM, early administration of fat-soluble vitamins needs to be further studied as a possible preventative measure against the development of DEP[ 12 ]. Additionally, serum levels of fat-soluble vitamins (vitamin D in particular) may have the potential to be used as markers of risk of AP-related DM, as mentioned by Norbitt et al [ 19 ]. The connection comes from previous findings that vitamin D levels negatively correlated with AP severity indexes[ 19 , 34 ].…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation